ANALYSIS OF MARKETING STRATEGY IN DEALING WITH THE COVID-19 PANDEMIC: (Case Study In Gema Insani Publishing Company) - Anita Rahmawati; Sri Isti Untari; Kristin Lukitaningrum (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
The year 2020 was shaken by the spread of the Covid-19 virus. The viral pandemic occurred has changed the way of life of the world, at least from a social and economic perspective. Predictions of a recession began to emerge as the economy weakened due to the spread of the virus forcing large parts of the population to be laid off. Many businesses experience losses and even go out of business, or at least experience a decline in profits (Brewer, 2020). The economic impact of this disaster is likely to continue for several years to come. Gema Insani is a publishing company in Depok which has been directly affected by the pandemic. A proper marketing strategy is needed so that even if there is a decline in the level of product sales, the decline is still under control or does not cause the company to go out of business. This study aims to analyze the marketing strategies that the Gema Insani company implemented during the pandemic. The research was conducted using qualitative methods and descriptive analysis. It can be concluded from the research results that the applied marketing strategy includes the marketing mix of product aspects, price, place, promotion, people, process and physical evidence. The most dominant aspect in dealing with and adapting to pandemic situation is  promotion aspect, that is by optimizing online marketing and product sales (digital marketing). By optimizing digital marketing, online product sales increased by 30%.